Development of a microsatellite panel for identification of biological samples of moose (Alces alces) in forensic research - Nedzvedskaya, Diana E.; Kotava, Sviatlana A.; Zabauskaya, Tatsiana V.; Rybakova, Veronika I.; Hrebianchuk, Aliaksandra Ya.; Tsybovsky, Iosif S. (Experimental Biology and Biotechnology, 2022)
For forensic analysis of evidence from illegal hunting sites of moose, a panel of 15 microsatellite (4 tetranucleotide and 11 dinucleotide) loci and 1 sex locus (amelogenin) was proposed. The cumulative power of discrimination of individual based on the common genetic database of moose (for a panel of 15 microsatellite loci) is more than 99.999 999999 999 %. The genetic and forensic indicators of a microsatellite panel were evaluated on a population sample of moose on a national scale (383 samples) for the first time in Europe and forensic methodology of the DNA identification of the moose (Alces alces) introduced into the national legal system.